2019
DOI: 10.1007/s42452-019-1207-8
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal action of Lippia alba essential oil in Rhizoctonia solani disease management

Abstract: Plant pathogens damage agriculture sector to a large extent, resulted in poor crop yield and quality. A well followed practice to curb plant diseases are mostly involved with application of conventional fungicides (synthetic chemical). However, their continuous and uncontrolled use has emerged as big challenge for humans due to the hazardous effect to the environment. This can also leads to the development of resistance to plant pathogens. Green chemistry based approaches have revolutionized the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Another disadvantage is that elevated pressure requires a more considerable upfront capital expenditure. Stashenko et al, 2004;Braga et al, 2005;Lima Juiz et al, 2015;Santos et al, 2016;Saroj et al, Antioxidant and antimicrobial activity (Patel et al, 2006;Janet et al, 2015;Baptista et al, 2018;Dzamic et al, 2009) Eugenia caryophyllata Thunb; Myrtaceae (Buds, leaves, and stems) Clove Eugenol, eugenol acetate, trans-caryophyllene Antioxidant, antimicrobial and anti-inflammatory activity (Sohlait, 2015;Wenqiang et al, 2007;Ivanovic et al, 2011;Mahboubi and Mahboubi, 2015;Sohilait et al, 2018;Öztürk and Özbek, 2005).…”
Section: Supercritical Fluid Extractionmentioning
confidence: 99%
“…Another disadvantage is that elevated pressure requires a more considerable upfront capital expenditure. Stashenko et al, 2004;Braga et al, 2005;Lima Juiz et al, 2015;Santos et al, 2016;Saroj et al, Antioxidant and antimicrobial activity (Patel et al, 2006;Janet et al, 2015;Baptista et al, 2018;Dzamic et al, 2009) Eugenia caryophyllata Thunb; Myrtaceae (Buds, leaves, and stems) Clove Eugenol, eugenol acetate, trans-caryophyllene Antioxidant, antimicrobial and anti-inflammatory activity (Sohlait, 2015;Wenqiang et al, 2007;Ivanovic et al, 2011;Mahboubi and Mahboubi, 2015;Sohilait et al, 2018;Öztürk and Özbek, 2005).…”
Section: Supercritical Fluid Extractionmentioning
confidence: 99%
“…Fungi such as Aspergillus spp., Botrytis cinerea , Colletotrichum capsici , Fusarium oxysporum , F. solani , R. solani , and Sclerotinia sclerotiorum reduce shelf life and market values for food commodities. Also, there is the danger caused by mycotoxins to human health (Saroj et al., 2019; Silva Bomfim et al., 2020).…”
Section: A Meta‐analysis By Somsmentioning
confidence: 99%
“…Among the oxygenated compounds, phenols, alcohols, aldehydes, ketones, esters, and oxides are the main classes compounds (Bazargani & Rohloff, 2016; Khan et al., 2019). Terpenes and their oxygenated derivatives, terpenoids, are often the main constituents of EOs, followed by phenylpropanoids (Bassolé & Juliani, 2012; Saroj et al., 2019). Furthermore, monoterpenes comprise almost 90% of the oils' composition, covering an extensive range of structures (Bakkali et al., 2008).…”
Section: A Meta‐analysis By Somsmentioning
confidence: 99%
“…These constituents have potent pesticidal compounds, as evidenced by both in vivo and in vitro studies demonstrating their efficacy 10,11 . Recent studies have reported the antimicrobial and antifungal efficacy of plant extracts against phytopathogenic fungi and associated fungal diseases 12,13,14 . The plant extracts from Andrographis paniculata Wall, Backhousia citriodora F.…”
Section: Introductionmentioning
confidence: 99%